P2X7 Receptor Upregulation in Huntington’s Disease Brains - Ollà, Ivana; Santos-Galindo, María; Elorza, Ainara; Lucas, José J. (Frontiers in Molecular Neuroscience, 2020)
Huntington’s Disease (HD) is a fatal degenerative disorder affecting the nervous system. It is characterized by motor, cognitive and psychiatric dysfunctions, with a late onset and an autosomal dominant pattern of inheritance. HD causing mutation consists on an expansion of repeated CAG triplets in the huntingtin gene (HTT), encoding for an expanded polyglutamine (polyQ) stretch in the huntingtin protein (htt). The mutation causes neuronal dysfunction and loss through multiple mechanisms, affecting both nucleus and cytoplasm. P2X7 receptor (P2X7R) emerged as a major player in neuroinflammation, since ATP -its endogenous ligand- is massively released under this condition. Indeed, P2X7R stimulation in the central nervous system (CNS) is known to enhance the release of pro-inflammatory cytokines from microglia and of neurotransmitters from neuronal presynaptic terminals, as well as to promote apoptosis. Previous experiments performed with neurons expressing the mutant huntingtin and exploiting HD mouse models demonstrated a role of P2X7R in HD. On the basis of those results, here we explore for the first time the status of P2X7R in HD patients’ brain. We report that in HD post-mortem striatum, as earlier observed in HD mice, the protein levels of the full-length form of P2X7R, also named P2X7R-A, are upregulated. In addition, the exclusively human naturally occurring variant lacking the C-terminus region, P2X7R-B, is upregulated as well. As we show here, this augmented protein levels can be explained by elevated mRNA levels. Furthermore, in HD patients’ striatum, P2X7R shows not only an augmented total transcript level, but also an alteration of its splicing. Remarkably, P2X7R intron 10-11 is more retained in HD patients when compared with controls. Taken together, our data confirm that P2X7R is altered in brains of HD subjects and strengthen the notion that P2X7R may represent a potential therapeutic target for HD.